1993
DOI: 10.1172/jci116647
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes underlying compensatory increase of diffusing capacity after left pneumonectomy in adult dogs.

Abstract: To determine if the functional compensation in diffusing capacity of the remaining lung following pneumonectomy is due to structural growth, we performed morphometric analysis of the right lung in three adult foxhounds -2 yr after left pneumonectomy (removal of 42% of lung) and compared the results to those in normal adult dogs previously studied by the same techniques. Diffusing capacity was calculated by an established morphometric model and compared to physiologic estimates at peak exercise in the same dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
10

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 27 publications
5
51
1
10
Order By: Relevance
“…1 c), the alveolar spaces and mean septal thickness were normal. The alveolar enlargement previously reported in adult dogs after left pneumonectomy (3) was less evident in dogs after right pneumonectomy, either at 5 or 16 mo.…”
Section: Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…1 c), the alveolar spaces and mean septal thickness were normal. The alveolar enlargement previously reported in adult dogs after left pneumonectomy (3) was less evident in dogs after right pneumonectomy, either at 5 or 16 mo.…”
Section: Resultscontrasting
confidence: 50%
“…It is generally believed that postpneumonectomy compensatory lung growth occurs in immature dogs but not in fully mature dogs (1)(2)(3). In adult dogs, postpneumonectomy compensation is largely attributed to use of existing functional reserves in the remaining lung.…”
Section: Introductionmentioning
confidence: 99%
“…As long as the remaining lung is relatively normal, this modest diffusion limitation is readily tolerated. Comparable diffusion impairment in well-trained adult dogs following left pneumonectomy (45% lung resection) elicits a budding alveolar cellular response but no overt growth of septal tissue [11,12]. The remaining lung increases by nearly 80% in volume; alveolar capillaries are enlarged, as would be expected from an increased blood flow.…”
Section: Pneumonectomy: a Model Of Compensatory Lung Growthmentioning
confidence: 94%
“…Although detailed quantitative morphological studies demonstrated that alveolar and capillary surface area, alveolar septal tissue volume and morphometric lung diffusing capacity are completely restored after PNX [15,17,18], the structural basis of how new alveolar tissue is added remains incompletely understood [5]. In particular, it is unclear whether regeneration is accomplished solely by growth of existing alveoli, as indicated by early studies [18][19][20], or if neoalveolarisation contributes to the restoration of lung parenchyma.…”
mentioning
confidence: 99%